Spermatozoa of tapeworms (Platyhelminthes, Eucestoda): advances in ultrastructural and phylogenetic studies - Levron, Céline; Miquel, Jordi; Oros, Mikulás; Scholz, Tomás (Biological reviews of the Cambridge Philosophical Society, 2010)
New data on spermiogenesis and the ultrastructure of spermatozoa of 'true' tapeworms (Eucestoda) are summarized. Since 2001, more than 50 species belonging to most orders of the Eucestoda have been studied or reinvestigated, particularly members of the Caryophyllidea, Spathebothriidea, Diphyllobothriidea, Bothriocephalidea, Trypanorhyncha, Tetraphyllidea, Proteocephalidea, and Cyclophyllidea. A new classification of spermatozoa of eucestodes into seven basic types is proposed and a key to their identification is given. For the first time, a phylogenetic tree inferred from spermatological characters is provided. New information obtained in the last decade has made it possible to fill numerous gaps in the character data matrix, enabling us to carry out a more reliable analysis of the evolution of ultrastructural characters of sperm and spermiogenesis in eucestodes. The tree is broadly congruent with those based on morphological and molecular data, indicating that convergent evolution of sperm characters in cestodes may not be as common as in other invertebrate taxa. The main gaps in the current knowledge of spermatological characters are mapped and topics for future research are outlined, with special emphasis on those characters that might provide additional information about the evolution of tapeworms and their spermatozoa. Future studies should be focused on representatives of those major groups (families and orders) in which molecular data indicate paraphyly or polyphyly (e.g. 'Tetraphyllidea' and Trypanorhyncha) and on those that have a key phylogenetic position among eucestodes (e.g. Diphyllidea, 'Tetraphyllidea', Lecanicephalidea, Nippotaeniidea).
Keywords: Cestoda; mužské pohlaví; biologická evoluce; druhová specificita; zvířata; Biological Evolution; Spermatozoa; Phylogeny; fylogeneze; spermie; Male; Species Specificity; Animals